Use of Thermosetting Binders for 3D Printing of Cemented Carbide or Cermet Bodies
The use of a water-soluble thermosetting binder system with organic non-aromatic materials addresses the challenges of porosity and green strength in carbide and cermet bodies, enhancing printing outcomes and environmental sustainability.
Patent Information
- Application Number
- JP2022535806
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-09
AI Technical Summary
Existing binder injection technologies for carbide and cermet bodies face challenges such as porosity issues in sintered bodies, low green strength, and the use of environmentally unfriendly binders, as well as solubility limitations and solvent-related problems during printing.
A water-soluble thermosetting binder system comprising organic non-aromatic materials with multiple hydroxyl and carboxyl groups, which react at high temperatures to form crosslinked ester bonds, enhancing green strength and reducing porosity, while being environmentally friendly and allowing for higher concentration use with less solvent.
The proposed binder system significantly improves the green strength of carbide and cermet bodies, reduces porosity, and allows for higher concentration use with less solvent, addressing the limitations of existing technologies while being environmentally friendly.
Smart Images

Figure 0007667157000001 
Figure 0007667157000002 
Figure 0007667157000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the use of a water-soluble thermosetting binder for binder jetting of cemented carbide and cermet green bodies, the water-soluble thermosetting binder comprising compound A, which is at least one organic non-aromatic substance containing at least two hydroxyl groups, and compound B, which is at least one organic non-aromatic substance containing at least two carboxyl groups, compound A and compound B being monomers or oligomers. [Background technology]
[0002] Additive manufacturing, also known as 3D printing, generally involves printing and bonding one layer at a time using specialized systems. Specifically, a layer of material may be deposited onto a working surface of a build chamber and bonded with another layer of the same or different material. Additive manufacturing may be used to produce articles from computer-aided design models using techniques such as, but not limited to, powder bed fusion (PBF), direct metal laser sintering (DMLS), or binder jet 3D printing.
[0003] The additive manufacturing of hardmetal or cermet bodies is preferably carried out by 3D printing techniques, which first produce a green body and then sinter the green body in a separate furnace, binder jetting being the most common type of such 3D printing technique.
[0004] When printing cemented carbide and cermet bodies using binder jetting, the strength of the printed object, i.e., green strength, must be sufficient to avoid breakage of the object during subsequent handling, e.g., powder removal, moving the object to a sintering furnace, etc.
[0005] Thermosetting binders, i.e. chemical binders that react at high temperatures, are known in binder jetting of powders. In some applications, one component is added together with the powder and the other component is added during printing, after which the printed object is cured. In the case of hardmetal and cermet powders this is a disadvantage, since one of the main problems is the porosity of the sintered body. The addition of one component to the powder can reduce the contact between the powders, increase the porosity or lead to binder-rich areas in the sintered state.
[0006] Thermosetting binders containing different types of polymers are the most common, however the concentration of the polymers must be kept low for solubility reasons and large amounts of solvent are added during printing, which can cause problems when drying the printed object.
[0007] Epoxy binders also exist, but these are generally not environmentally or health friendly.
[0008] Another type of binder used in binder jetting is one in which the polymers intertwine rather than react chemically during curing, thereby increasing green strength. These binders can be dissolved by the cleaning fluid if wet powder removal is used, and therefore the green body will lose its strength.
[0009] U.S. Patent Application Publication No. 2019 / 0054527, for example, describes a binder for binder jetting of ceramics that includes two different polymers, which non-covalently bonds the two different types of polymers during curing. Summary of the Invention
[0010] One object of the present invention is to obtain a less hazardous binder.
[0011] Another object of the present invention is to obtain a binder for binder jetting that can be added in higher concentrations, i.e., with less solvent.
[0012] Another object of the present invention is to obtain a binder for binder jetting that provides increased green strength.
[0013] Another object of the present invention is to have a binder for binder jetting that does not dissolve after curing, i.e., during powder removal, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention relates to the use of a water-soluble thermosetting binder for binder jetting of cemented carbide or cermet green bodies, the water-soluble thermosetting binder comprising compound A, which is at least one organic non-aromatic substance containing at least two hydroxyl groups, and compound B, which is at least one organic non-aromatic substance containing at least two carboxyl groups, compound A and compound B being monomers or oligomers with a molecular weight of less than 2000 g / mol.
[0015] By thermosetting binder, it is meant herein that the ingredients in the binder harden by curing, which is usually induced by the application of heat.
[0016] The thermosetting binder comprises compound A and compound B, and optionally other additives such as pH adjusters, surfactants, etc. Compounds A and B should have slow or no reaction rate at room temperature to obtain a reasonable shelf life.
[0017] Compounds A and B are both water-soluble. Water-soluble herein means that compounds A and B described herein are soluble in water in the amounts shown below. Compounds A and B are both monomers or oligomers. Oligomer herein means a compound with a molecular weight of less than 2000 g / mol, preferably less than 1000 g / mol.
[0018] Compounds A and B are also non-aromatic, which means herein that compounds A and B do not contain aromatic groups, such as benzyl groups, phenyl groups, etc. Aromatic materials are undesirable as they may form deleterious by-products during debinding and / or sintering.
[0019] Compounds A and B react by crosslinking and forming ester bonds to form a green body with high strength after the green body is exposed to high temperatures during curing.
[0020] Compound A consists of at least one organic non-aromatic substance containing at least two hydroxyl groups, and compound A is a monomer or an oligomer. Compound A can be constituted only by a single organic non-aromatic substance containing at least two hydroxyl groups, or it can be a mixture of two or more organic non-aromatic substances containing at least two hydroxyl groups.
[0021] In one embodiment of the present invention, the at least one organic non-aromatic material comprising at least two hydroxyl groups does not comprise an epoxy group.
[0022] In one embodiment of the present invention, the at least one organic non-aromatic material containing at least two hydroxyl groups does not contain nitrogen, phosphorus, silicon, potassium, sodium, or fluorine.
[0023] In one embodiment of the invention, compound A is a polyol, such as a diol, triol, or tetriol, more preferably compound A is selected from the group of propylene glycol, glycerin, maltodextrin, erythritol, xylitol, sorbitol, and mannitol, most preferably compound A is selected from glycerin and maltodextrin.
[0024] Compound B consists of at least one organic non-aromatic substance containing at least two carboxyl groups and is a monomer or oligomer. Compound B can be constituted only by a single organic non-aromatic substance containing at least two carboxyl groups or can be a mixture of two or more organic non-aromatic substances containing at least two carboxyl groups.
[0025] In one embodiment of the present invention, the at least one organic non-aromatic material comprising at least two carboxyl groups does not comprise an epoxy group.
[0026] In one embodiment of the present invention, the at least one organic non-aromatic material containing at least two carboxyl groups does not contain nitrogen, phosphorus, silicon, potassium, sodium, or fluorine.
[0027] In one embodiment of the present invention, the at least one organic non-aromatic substance containing at least two carboxyl groups is selected from the group of citric acid, tartaric acid, succinic acid, fumaric acid, maleic acid, and carballylic acid, polyacrylic acid oligomers, most preferably compound B is citric acid.
[0028] The amounts of compounds A and B are such that the molar ratio of hydroxyl groups in compound A to carboxyl groups in compound B is between 0.1 and 10, preferably between 0.5 and 2.0, most preferably between 0.8 and 1.2.
[0029] In one embodiment of the present invention, the total amount of compound A and compound B is between 2 and 80% by weight, preferably between 30 and 80% by weight, most preferably between 30 and 50% by weight.
[0030] In one embodiment of the invention, the total amount of compounds A and B is greater than 80% by weight of the "dry" components, ie, excluding solvent.
[0031] The thermosetting binder may also contain other additives, such as surfactants, pH adjusters, such as ethanol, ethylene glycol, ethylene glycol monobutyl ether.
[0032] Compounds A and B, together with other additives if added, are dissolved in a solvent. Preferably, the solvent is aqueous, i.e., the solvent contains more than 50% water by volume, preferably more than 60% water by volume, and most preferably, the solvent is 100% water.
[0033] In one embodiment of the invention, the binder comprises glycerin in an amount between 35 and 50% by weight, and citric acid in an amount between 15 and 25% by weight.
[0034] In one embodiment of the present invention, the binder may be used together with other binders to further increase the green strength, in which case the total amount of compounds A and B must be at least 2% by weight of the total amount of binder.
[0035] The present invention also relates to a method for producing a hardmetal or cermet body using the binder described above, said method comprising the following steps: Providing a print-ready hardmetal or cermet powder; providing a water soluble thermosetting binder; printing said powder onto a green body by binder jetting technique; hardening the body by heating at a temperature between 100°C and 250°C. sintering the green body. Including, The water-soluble two-component binder comprises compound A, which is at least one organic non-aromatic substance containing at least two hydroxyl groups, and compound B, which is at least one organic non-aromatic substance containing at least two carboxyl groups, and compound A and compound B are monomers or oligomers.
[0036] The term "cermet" is intended herein to denote a material comprising hard constituents in a metallic binder phase, the hard constituents comprising carbides or carbonitrides of one or more of Ta, Ti, Nb, Cr, Hf, V, Mo, and Zr, e.g., TiN, TiC, and / or TiCN.
[0037] The term "hard metal" is intended herein to denote a material comprising a hard component in a metallic binder phase, the hard component comprising at least 50% by weight of WC particles. The hard component may also comprise carbides or carbonitrides of one or more of Ta, Ti, Nb, Cr, Hf, V, Mo, and Zr, such as TiN, TiC, and / or TiCN.
[0038] The metallic binder phase in the cermet or cemented carbide is a metal or a metal alloy, where the metal may be selected from, for example, Cr, Mo, Fe, Co, or Ni, either alone or in any combination. Preferably, the metallic binder phase comprises a combination of Co, Ni, and Fe, a combination of Co and Ni, or only Co. The metallic binder phase may comprise other suitable metals known to those skilled in the art. The average content of the metallic binder phase in the powder is 4-15% by weight, preferably 8-13% by weight or 10-13% by weight.
[0039] The print-ready powder used in the method for producing a three-dimensional print of a cermet or hardmetal body may be any powder of cermet or hardmetal particles suitable for three-dimensional printing.
[0040] By cermet or cemented carbide particles it is meant herein that the particles are pre-sintered, which means herein that the powder has been sintered, such as by using solid phase sintering and / or liquid phase sintering.
[0041] Preferably, the print-ready powder is a pre-sintered powder consisting of spherical cermet or cemented carbide particles with good flowability.
[0042] In one embodiment of the invention, the D50 of the cemented carbide and / or cermet particles is between 5 and 35 μm, preferably between 10 and 30 μm, more preferably between 15 and 25 μm, and most preferably between 17 and 21 μm.
[0043] In one embodiment of the present invention, the print-ready powder is pre-sintered to provide a porosity of the cermet or cemented carbide particles between 0 and 40%, preferably between 5 and 20% or between 15 and 20% by volume.
[0044] In one embodiment of the present invention, the print-ready powder is pre-sintered such that the porosity of the cermet or cemented carbide particles is between 0 and 20% porosity, preferably between 0 and 10% or between 0 and 5% by volume, or such that the particles are fully dense.
[0045] The particular porosity can potentially contribute to sintering activity during sintering of the printed green body, and the porosity can be adjusted depending on the degree of sintering activity desired for a particular cermet or hardmetal composition. Porosity can be measured, for example, by LOM at 1000x magnification.
[0046] In one embodiment of the present invention, the print-ready powder comprises: Mixing the cermet or cemented carbide raw material powder with an organic binder Spray drying the raw powder, thereby forming a granulated raw powder. pre-sintering the spray dried raw powder to remove the organic binder, thereby forming a pre-sintered granulated powder; Pre-treating the pre-sintered granulated powder until a desired particle size distribution is obtained, thereby forming a print-ready powder. Manufactured by.
[0047] By pre-treatment it is meant here that the pre-sintered granulated powder is deagglomerated, as the granules may gather in clusters, which may cause problems during printing. This can be done by a gentle milling step. If further adjustment of the particle size is required, the milling step can be extended.
[0048] In one embodiment of the invention, the spray dried powder is sieved prior to the pre-sintering step, preferably to remove particles larger than 42 μm in diameter, which is advantageous in reducing potential problems with very large particles in the powder.
[0049] In one embodiment of the present invention, the print-ready powder consists of cemented carbide particles. The cemented carbide particles include WC with an average particle size of 0.5-5 μm or 0.5-2 μm. Preferably, more than 80 wt. % of the hard components is WC.
[0050] In one embodiment of the present invention, the print-ready powder consists of cemented carbide particles containing WC and Co in an amount between 10 and 13 wt.%. The cemented carbide particles have a D50 between 17 and 21 μm and a porosity between 0 and 5 vol.%.
[0051] Binder jetting is a well-known and relatively inexpensive 3D printing method that involves first applying a layer of powder, selectively depositing a binder onto the powder layer, and then building, layer by layer, a green body having the desired shape.
[0052] Curing is usually performed after the printing process. The thermosetting binder cures so that the green body has sufficient green strength. Curing can be performed by subjecting the printed green body to an elevated temperature between 100 and 250°C, preferably between 140°C and 200°C, for between 1 and 100 hours, preferably between 1 and 5 hours, before removing the excess powder. In one embodiment, curing is performed in a non-oxidizing environment, such as Ar or N2, and / or at low pressure or vacuum.
[0053] After the curing step, all excess powder is removed from the green body by a powder removal step. Powder removal can be a dry process, i.e. the excess powder is for example blown off and brushed off the green body. Powder removal can also be a wet process, i.e. immersing the green body in any kind of solvent and simply washing off the excess powder. Also, vibration, e.g. ultrasound, can be used for both dry and wet powder removal.
[0054] The green body is then sintered in a sintering furnace by liquid phase sintering, which is carried out at a temperature higher than the temperature at which the metal binder in the particular cermet or hardmetal composition melts. Preferably, the liquid phase sintering is carried out at a temperature between 1350° C. and 1500° C. Preferably, the duration of the liquid phase sintering is between 30 and 300 minutes, more preferably between 30 and 120 minutes.
[0055] The liquid phase sintering process is preferably carried out in vacuum, i.e. so-called vacuum sintering, which means in this specification that the pressure is less than 0.5 mbar.
[0056] Liquid phase sintering processes are common in the art of sintering cermets and hard metals and usually include a debinding step at a temperature between 200° C. and 550° C. for between about 30 and 120 minutes before the liquid phase sintering temperature is reached. The debinding step is carried out to remove residual binders, e.g. thermosetting printing binders.
[0057] In one embodiment of the invention, the cemented carbide or cermet body produced according to the invention is a cutting tool, such as an insert, a drill, or an end mill.
[0058] In one embodiment of the present invention, the cemented carbide or cermet body manufactured according to the present invention can be a wear part, such as a nozzle, a seal ring, a pump impeller, a flow controller for oil / gas, etc. EXAMPLES
[0059] Example 1 Green bodies in the shape of rectangular blocks of 60x15x5 mm were printed from a pre-sintered cemented carbide powder containing mostly spherical granules with D10 of 11.1 μm, D50 of 20.3 μm and D90 of 33.6 μm. The composition of the powder was 12 wt% Co and balance WC. The average porosity of the granules was 0 vol% or very close to 0.
[0060] The binder was prepared by mixing water, ethanol, glycerin, and citric acid. The components were thoroughly stirred until all components were dissolved. The composition is shown in Table 1. The molar ratios in Table 1 are the molar ratios of hydroxyl groups in compound A to carboxyl groups in compound B. Table 1 TIFF0007667157000001.tif23170
[0061] Printing was performed with a binder jetting printer with a layer thickness of 50 μm during printing. Powder printing was performed with an "ExOne Innovent+". The saturation during printing was 110% and the magnification of the part was set to 1.
[0062] The saturation of the print binder is defined as the percentage of void volume filled with the print binder at a specified powder packing density (here, the powder packing density is set to 60%). A higher saturation is required to print with powders containing a high percentage of porous particles compared to a low percentage of porous particles.
[0063] During printing, the sequence of each layer was as follows: a 50 μm powder layer was spread on the bed, the printed binder was spread in a pattern defined in the CAD model, and then the printed binder was dried to remove all or part of the solvent of the printed binder. This was repeated until the full height of the green body was printed. Afterwards, curing was carried out overnight at 200 °C in vacuum. Powder removal was done manually with a brush and compressed air.
[0064] Example 2 The green bodies were printed using the same process and cemented carbide powders described in Example 1, except that the binder was prepared by mixing maltodextrin (dextrose equivalent about 18) and citric acid with a commercial aqueous binder, and the saturation during printing was 100%. The ingredients were thoroughly stirred until all the maltodextrin and citric acid were dissolved. The composition is shown in Table 2. The molar ratios in Table 2 are the molar ratios of hydroxyl groups in compound A to carboxyl groups in compound B. Table 2 TIFF0007667157000002.tif23170
[0065] For comparison, a green body using only a commercial aqueous binder was printed using the same powder and process as in Example 2.
[0066] Example 3 After powder removal, the strength of the green bodies was tested by a transverse bending test with a speed of 10 mm / min and a preload of 0.05 N. The results are shown in Table 3. Table 3 TIFF0007667157000003.tif30170
[0067] In Table 3 it can be clearly seen that the green bodies using the binders according to the invention, i.e. Inventive 1 and Inventive 2, show a significant improvement in green strength compared to the commercial water-based binders.
Claims
1. 1. Use of a water-soluble thermosetting binder for binder jetting of cemented carbide or cermet green bodies, the water-soluble thermosetting binder comprising compound A, which is at least one organic non-aromatic substance comprising at least two hydroxyl groups, and compound B, which is at least one organic non-aromatic substance comprising at least two carboxyl groups, compound A and compound B being monomers or oligomers with a molecular weight of less than 2000 g / mol, the total amount of compounds A and B being between 30 and 80 wt.%, compounds A and B do not comprise epoxy groups, and compounds A and B do not comprise nitrogen, phosphorus, silicon, potassium, sodium, or fluorine.
2. 2. Use of a water-soluble thermosetting binder according to claim 1, wherein the amounts of compounds A and B are such that the molar ratio of hydroxyl groups in compound A to carboxyl groups in compound B is between 0.1 and 10.
3. 3. Use of the water-soluble thermosetting binder according to claim 1 or 2, wherein compound A is selected from propylene glycol, glycerin, maltodextrin, erythritol, xylitol, sorbitol and mannitol.
4. 4. Use of the water-soluble thermosetting binder according to any one of claims 1 to 3, wherein compound B is selected from citric acid, tartaric acid, succinic acid, fumaric acid, maleic acid, polyacrylic acid oligomers, and carballylic acid.
5. 5. Use of the water-soluble thermosetting binder according to any one of claims 1 to 4, wherein compound A is selected from glycerin or maltodextrin and compound B is citric acid.
6. 6. Use of a water-soluble thermosetting binder according to any one of claims 1 to 5, wherein the binder comprises glycerin in an amount between 35 and 50% by weight, citric acid in an amount between 15 and 25% by weight.
7. 1. A method for producing a cemented carbide or cermet body, comprising the steps of: Providing a print-ready hardmetal or cermet powder; providing a water soluble thermosetting binder; printing said powder onto a green body by binder jetting technique; hardening the green body by heating at a temperature between 100° C. and 250° C. sintering the green body. Including, 1. A method for preparing a water-soluble thermosetting binder comprising compound A, which is at least one organic non-aromatic substance containing at least two hydroxyl groups, and compound B, which is at least one organic non-aromatic substance containing at least two carboxyl groups, wherein compound A and compound B are monomers or oligomers having a molecular weight of less than 2000 g / mol, the total amount of compounds A and B is between 30 and 80% by weight, compounds A and B do not contain epoxy groups, and compounds A and B do not contain nitrogen, phosphorus, silicon, potassium, sodium, or fluorine.
8. 8. The method of claim 7, wherein the print-ready powder is a cemented carbide powder comprising a metal binder in an amount between 10 and 13 wt. %, the cemented carbide particles having a D50 between 17 and 21 μm and a porosity between 0 and 5 vol. %.
9. 9. The method of claim 8, wherein compound A is selected from propylene glycol, glycerin, maltodextrin, erythritol, xylitol, sorbitol, and mannitol.
10. 10. The method of claim 8 or 9, wherein compound B is citric acid, tartaric acid, succinic acid, fumaric acid, maleic acid, polyacrylic acid oligomers, and carballylic acid.
11. 11. The process according to any one of claims 8 to 10, wherein the amounts of compounds A and B are such that the molar ratio of hydroxyl groups in compound A to carboxyl groups in compound B is between 0.1 and 10.
12. 12. The method according to any one of claims 8 to 11, wherein compound A is selected from glycerin or maltodextrin and compound B is citric acid.
Citation Information
Patent Citations
Objects having cores with metal nanoparticle binders
WO2019027417A1